Inhibition of Hippocampal Neurogenesis Starting in Adolescence Increases Anxiodepressive Behaviors Amid Stress - Larivee, Rachelle; Johnson, Natalie; Freedgood, Natalie R.; Cameron, Heather A.; Schoenfeld, Timothy J. (Frontiers in Behavioral Neuroscience, 2022)
Stressors during the adolescent period can affect development of the brain and have long-lasting impacts on behavior. Specifically, adolescent stress impairs hippocampal neurogenesis and can increase risk for anxiety, depression, and a dysregulated stress response in adulthood. In order to model the functional effects of reduced hippocampal neurogenesis during adolescence, a transgenic neurogenesis ablation rat model was used to suppress neurogenesis during the adolescent period and test anxiodepressive behaviors and stress physiology during adulthood. Wildtype and transgenic (TK) rats were given valganciclovir during the first two weeks of adolescence (4-6 weeks old) to knock down neurogenesis in TK rats. Starting in young adulthood (13 weeks old), blood was sampled for corticosterone at several time points following acute restraint stress to measure negative feedback of the stress response, and rats were tested on a battery of anxiodepressive tests at baseline and following acute restraint stress. Although TK rats had large reductions in both cell proliferation during adolescence, as measured by bromodeoxyuridine (BrdU), and ongoing neurogenesis in adulthood (by doublecortin), resulting in decreased volume of the dentate gyrus, negative feedback of the stress response following acute restraint was similar across all rats. Despite similar stress responses, TK rats showed higher anxiety-like behavior at baseline. In addition, only TK rats had increased depressive-like behavior when tested after acute stress. Together, these results suggest that long-term neurogenesis ablation starting in adolescence produces hippocampal atrophy and increases behavioral caution and despair amid stressful environments.